Cooperative Transmission Mechanisms in Next Generation WiFi: IEEE 802.11ac. (28th January 2014) - Ji, Baofeng; Song, Kang; Hu, Ying; Chen, Hongjun
Abstract : Very high throughput (VHT) WLAN, known as IEEE 802.11ac, can provide compelling performance and has attracted extensive attention for achieving transmission rate over 1 G bps for 5 GHz band owing to involving the MU-MIMO and maximum 160 MHz bandwidth transmission. Despite extensive studies and dramatic performance, the conventional carrier sensing mechanism emerges some drawbacks especially in the overlapping BSS scenario responsible for employment of MU-MIMO and bandwidth expansion. In order to address the issue of conventional carrier sensing mechanism, namely, redundant or useless network allocation vector (NAV) setting, this paper proposes an enhanced NAV transmission mechanism, which not only needs little modifications to current standard draft but also can achieve performance improvement significantly. On this basis, in order to solve the SINR inaccuracy calculated based on null data packet (NDP) in the actual MU-MIMO transmission, the SINR feedback mechanism is proposed and the frame structure modifications are displayed in detail. Furthermore, theoretical analysis is also performed on the proposed mechanism and the formulas of the achieved gains are also derived. Numerical results confirm the validation of our theoretical analysis and further substantiate that the proposed scheme obtains obvious throughput gain over the conventional mechanism.